Invólucro Virtual a Mídia digital como Extensão da Mente - Machado, Silvio Wander (2009)
This work has its central key on the issues of dematerialization or virtual representation. What the new possibilities of creation through the use of digital media would be, and if these possibilities would create new aesthetic concepts, are questions that I try to answer throughout this dissertation. As groundwork for this research, a photographic essay, work of my own, called Invólucro Virtual, Virtual Housing‟, was used. The essay is an excursion into the picture prompted by the idea of virtual representation of envelopes in bodies, through the use of technological resources. They are representations and insights of a universe where the intangible, the volatile and fluidity reside, which occur through the hybridization of digital resources that make it possible to merge an image of the bitmap with scripts for software manipulation. Such possibilities, as the unsetting characteristics of these configurations and their moving condition represent, in my opinion, the very object of my research: the use of digital media as an extension of the mind